Cross-efficiency evaluation in the presence of flexible measures with an application to healthcare systems - Abolghasem, Sepideh; Toloo, Mehdi; Amézquita, Santiago (Health care management science, 2019)
In recent years, most countries around the world have struggled with the consequences of budget cuts in health expenditure, obliging them to utilize their resources efficiently. In this context, performance evaluation facilitates the decision-making process in improving the efficiency of the healthcare system. However, the performance evaluation of many sectors, including the healthcare systems, is, on the one hand, a challenging issue and on the other hand a useful tool for decision- making with the aim of optimizing the use of resources. This study proposes a new methodology comprising two well-known analytical approaches: (i) data envelopment analysis (DEA) to measure the efficiencies and (ii) data science to complement the DEA model in providing insightful recommendations for strategic decision making on productivity enhancement. The suggested method is a first attempt to combine two DEA extensions: flexible measure and cross-efficiency. We develop a pair of benevolent and aggressive scenarios aiming at evaluating cross-efficiency in the presence of flexible measures. Next, we perform data mining cluster analysis to create groups of homogeneous countries. Organizing the data in similar groups facilitates identifying a set of benchmarks that perform similarly in terms of operating conditions. Comparing the benchmark set with poorly performing countries we can obtain attainable goals for performance enhancement which will assist policymakers to strategically act upon it. A case study of healthcare systems in 120 countries is taken as an example to illustrate the potential application of our new method.
Keywords: Clustering; Flexible measure; Models, Statistical; Data science; Decision Making; alokace zdrojů; Global Health; celosvětové zdraví; shluková analýza; lidé; statistické modely; Efficiency, Organizational; Healthcare; efektivita organizační; Humans; poskytování zdravotní péče; Delivery of Health Care; rozhodování; Resource Allocation; Data envelopment analysis; Cluster Analysis; Cross-efficiency